(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
Despite a vast array of HIV/AIDS prevention communication initiatives in South Africa, recentresearch pointed out that the general public’s knowledge level about HIV/AIDS has decreasedand that risky behaviour associated with the spread of the virus, is on the increase. This meansthat even though some successes with HIV/AIDS prevention communication have been achieved,new innovative ways of communicating about the epidemic urgently needs to be investigated. Insearch for a new direction, this article maps four forms of HIV/AIDS prevention communicationin the country. Instead of continuing on the trajectory of exploring project-based campaigns thatare initiated ‘from the outside’ (such as projects formulated by donor institutions), this articlesuggests that community-initiated HIV/AIDS prevention communication initiatives might suggesta new direction to supplement existing communication on the epidemic.